Minkowski fractal tag antennas integrated with split ring resonators and complementary split ring resonators for radio frequency identification applications - Jalal, Ali Sadeq Abdulhadi (2013)
RFID stands for Radio Frequency Identification. The main goal of an RFID system is to carry data on a transponder (tag) that can be retrieved with a transceiver through a wireless connection. The contactless Identification (ID) system relies on data transmission via radio frequency electromagnetic (EM) signals, and consequently, the whole operation is non-line-of-sight and weather independent. These advantages overcome the limitations of optical barcodes, which are line-ofsight and weather dependent and need manual operation. Most RFID tags are comprised of an antenna and integrated circuit (IC). The IC performs all of the data processing and is powered by extracting power from the interrogation signal transmitted by the RFID reader. The tag antenna determines the amount of power transferred from the reader to the tag and back from the tag to the reader. Though there are no constraints on the physical parameters of the reader’s antenna, such as being planar or small in size, these constraints do apply on the tag’s antenna. In fact, the tag miniaturizing is limited by the tag antenna size. This thesis reports on the design, fabrication, and measurement of Ultra High Frequency (UHF) RFID tag antennas (860 to 960 MHz), which can be used in various applications. The proposed tag antennas are designed and fabricated to achieve low tagging costs, tagging of small objects at item level, as well as tagging metallic objects with miniaturized tags. First, it presents three different types of planar fractal RFID tag antenna designs integrated with square Split Ring Resonators (SRR) in an attempt to improve their performance characteristics at low cost. Three fractal iterations are considered to perform size reduction. Each antenna design was etched on FR4 epoxy substrate with an evident compact size. The antenna sizes are: 82 × 88.59 × 1.6 mm3 for AN1;72 × 78.59 × 1.6 mm3 for AN2 and 66.5 × 73.09 × 1.6 mm3 for AN3. The modified Minkowski fractal structure has been adopted to perform size reduction in three different iteration designs. Return loss results show that the integration of SRRs with antennas performs a frequency down-shift of the antenna resonant frequency thereby achieving further size reduction over the original fractal structure that was aimed for size reduction. The impedance of the designed antennas were simulated then measured to validate the design. The experiment results showed that the maximum read range of the proposed tag antennas, AN1, AN2 and AN3 is about 2.10 m, 1.10 m and 0.75 m respectively with 4.0 W EIRP radiation power of the RFID reader. The proposed RFID Tag antennas are compact, low cost, and with good reading rang that make them suitable for RFID applications. They are used for tagging objects other than metals or liquids. Second, two metal mount fractal tag antennas are designed and tested. The two antennas are integrated with square Complementary SRRs (CSRR) in a floating intermediate conductive copper layer. This floating layer achieves down shift to the antenna resonant frequency and enhances its gain due to the added capacitance from the CSRR structure. The size of the proposed tag antennas is 36.7×18.1×3.165 mm3 for antenna N1 and 35.3×17.4×3.165 mm3 for antenna N2. Very small and compact tag antennas are achieved with good agreement between measured and simulated impedance results. The read range measurements showed that the maximum read range of N1, and N2 is about 0.82 m and 0.48 m respectively, obtained when the two tags are placed on a square metallic sheet. The proposed RFID tag antennas offer attractive design for metallic objects identification such as gas cylinders and oil barrels tagging in petrol refineries.